2019
DOI: 10.1002/cncr.32120
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy inhibition overcomes sorafenib resistance in S45F‐mutated desmoid tumors

Abstract: Background Desmoid tumors (DTs) are rare and understudied fibroblastic lesions that are frequently recurrent and locally invasive. DT patients often experience chronic pain, organ dysfunction, decrease in quality of life, and even death. Methods Sorafenib has emerged as a promising therapeutic strategy, which has led to the first randomized phase 3 clinical trial devoted to DTs. Concurrently, we conducted a comprehensive analysis of sorafenib efficacy in a large panel of desmoid cell strains to probe for respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…In desmoid tumors, the S45F mutant β-catenin has been associated with higher recurrence rates, a poor response to meloxicam and decreased progression arrest after imatinib treatment [ 20 23 ]. In addition, our group recently showed that sorafenib-induced cell death in S45F mutated desmoid tumors appears to be associated with altered autophagy signaling pathway, and that these S45F mutants are dependent on autophagy as an antiapoptotic mechanism [ 38 ]. Notably, our results showing that apoptosis-related genes are deregulated in S45F mutant desmoid tumors support the hypothesis that these mutants do not rely on apoptosis as a mechanism of cell death and may explain why the autophagy pathway is applicable in these tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In desmoid tumors, the S45F mutant β-catenin has been associated with higher recurrence rates, a poor response to meloxicam and decreased progression arrest after imatinib treatment [ 20 23 ]. In addition, our group recently showed that sorafenib-induced cell death in S45F mutated desmoid tumors appears to be associated with altered autophagy signaling pathway, and that these S45F mutants are dependent on autophagy as an antiapoptotic mechanism [ 38 ]. Notably, our results showing that apoptosis-related genes are deregulated in S45F mutant desmoid tumors support the hypothesis that these mutants do not rely on apoptosis as a mechanism of cell death and may explain why the autophagy pathway is applicable in these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Annexin V-PI staining (BD Biosciences, San Jose, CA, USA) was used to measure cell cycle progression and apoptosis induction as previously described [ 45 ]. Caspase 3/7 apoptosis activity was measured using Incucyte software (Essen Biosciences, Ann Arbor, MI, USA) as previously described [ 38 ]. Briefly, fluorescence of caspase 3/7 substrate was divided by the total number of cells measured using Vybrant® DyeCycle™ Green stain (Life Technologies, Grand Island, NY, USA) to obtain the apoptotic index.…”
Section: Methodsmentioning
confidence: 99%
“…It is crucial to understand the precise molecular mechanisms underlying sorafenib resistance in order to identify novel therapeutic targets and improve the clinical outcome of HCC patients. Although, sorafenib-induced autophagy contributes to drug resistance, it is unknown whether hyperactivated mitophagy is also involved in sorafenib resistance in HCC [23][24][25]. Regarding hypoxia is a major stimulus of mitophagy and also an important cause of sorafenib resistance [26][27][28], our objective was to determine the potential relationship between mitophagy and hypoxia-induced sorafenib resistance in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…However, patients at an advanced stage are still faced with high rate of recurrence after surgery . Sorafenib, a multi‐tyrosine kinase inhibitor, is known to suppress tumor growth . In a previous study, sorafenib was found to exert an anticancer effect on cholangiocarcinoma, whereas, the chemoresistance was confirmed to worsen the 5‐year survival rate.…”
Section: Introductionmentioning
confidence: 99%